Rapidly labelled ribonucleic acid from rat liver. Studies in the attachment to ribosomes and stimulation of the incorporation of amino acids into polypeptides in cell-free systems - Wilkinson, B. R. (1966)
1. Rapidly labelled RNA from rat liver, either as a complex with DNA (m-RNA–DNA) or with ribosomal RNA (m-RNA–RNA) binds to ribosomes in the polysome region. No binding could be demonstrated with ribosomal RNA or native DNA from Bacillus subtilis. 2. With ribosomes from rat liver, Escherichia coli or hepatoma the m-RNA–DNA stimulated incorporation of amino acids with rat-liver ribosomes only, whereas the m-RNA–RNA complex was effective with ribosomes from E. coli or the hepatoma. 3. Polyuridylic acid was effective as messenger RNA with all three ribosomes but much greater stimulation was obtained with ribosomes from E. coli and the hepatoma. 4. The degree of incorporation of phenylalanine with polyuridylic acid and ribosomes from a hepatoma was decreased by about 50% when ribosomal RNA was present.